2023
DOI: 10.3390/pathogens12030498
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Detrimental Effects of Cigarette Smoke, Alcohol, and SARS-CoV-2 in COPD Bronchial Epithelial Cells

Abstract: Lung conditions such as COPD, as well as risk factors such as alcohol misuse and cigarette smoking, can exacerbate COVID-19 disease severity. Synergistically, these risk factors can have a significant impact on immunity against pathogens. Here, we studied the effect of a short exposure to alcohol and/or cigarette smoke extract (CSE) in vitro on acute SARS-CoV-2 infection of ciliated human bronchial epithelial cells (HBECs) collected from healthy and COPD donors. We observed an increase in viral titer in CSE- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Importantly, Muralidharan et al. studied the acute impact of short exposure to cigarette smoke extract and/or alcohol on SARS-CoV-2 infection of ciliated human bronchial epithelial cells of healthy subjects [19] , and found that viral titers were only increased in cells treated with both compounds but not with cigarette smoke extract or alcohol alone, thus emphasizing that cigarette smoke may only play a subsidiary role in the pathogenesis of COVID-19. Accordingly, the biological evidence that cigarette smoke alone would enhance the risk of infection and/or unfavorable disease progression remains weak, at best.…”
mentioning
confidence: 99%
“…Importantly, Muralidharan et al. studied the acute impact of short exposure to cigarette smoke extract and/or alcohol on SARS-CoV-2 infection of ciliated human bronchial epithelial cells of healthy subjects [19] , and found that viral titers were only increased in cells treated with both compounds but not with cigarette smoke extract or alcohol alone, thus emphasizing that cigarette smoke may only play a subsidiary role in the pathogenesis of COVID-19. Accordingly, the biological evidence that cigarette smoke alone would enhance the risk of infection and/or unfavorable disease progression remains weak, at best.…”
mentioning
confidence: 99%